Facial scar revision: A review and case report - Kandel, Shila; Dhungana, Ganesh (Hasanuddin University, 2023)
Objective: This study reviews surgical and non-surgical options for facial scar revision and presents two case reports with efficacious scar revision surgery.Methods: Surgical exposure and primary closure was performed under local anesthesia to revise the old scar.Results: Patients were kept on periodic follow up for 6 months after the procedure. The patients had a very good cosmetic result with this technique, as the scar was much less evident after a follow-up of 6 months.Conclusion: Facial scar revision is often considered as a cosmetic treatment aimed at creating a narrower and flatter scar that is less noticeable. Therefore, it is critical that clinicians have a thorough knowledge of facial anatomical structures, tissue repair, and the various basic and applied approaches to surgical scar revision, which include using an aseptic technique, careful tissue manipulation, sharp anatomic sectioning of the tissue, cauterization of dead spaces and careful hemostasis.